Examining fish movement in terms of advection or diffusion: a case study of northeastern Atlantic cod - Lundgreen, RBC; Nielsen, A; Krüger-Johnsen, M; Righton, D; Mion, M; Radtke, K; Plikshs, M; Leskelä, AJ; Raitaniemi, J; Griffiths, CA; Casini, M; Krumme, U; et al. (Marine Ecology Progress Series, 2022)
Advection (directional movement) and diffusion (dispersed movement) were applied for the first time to describe movement patterns in Atlantic cod in the North Sea and Baltic Sea between 1955 and 2020. The advection−diffusion approach provided more detailed estimates of movement that corresponded to previously observed patterns using different analytical techniques. Spatial patterns were evident with greater movement distances in cod from the North Sea and eastern Baltic Sea compared to the western Baltic and Kattegat−Skagerrak. Furthermore, comparative case studies on different ecotypes in the western and eastern Baltic suggested that inshore cod were more resident compared to offshore cod. This preliminary study highlights the usefulness of the advection−diffusion method to describe movements in fish populations, and can be further expanded by incorporating information on environment and mortality and providing information to spatially explicit population models.